The archetypical analysis of i?bni sina stories - Şimşek, Esma; Şenocak, Ebru (My University, 2009)
According to Carl Gustav Jung, the archetypes are internal factors that creates the collective unconscious of the humankind. The origin of archetypes can be treced back through myths. Along with this they can be analyzed with the Joseph Campbell's seperation, progress and return formula. The archetypes are encoded in these narrative genres like legends, tales and folk stories and inferred with symbols that distinguishes the hero's journey. İbni Sina known as a philosopher, physician, mathematician, doctor, poet, traveller and scientist the history of Turkish culture. However, in the work called İbni Sina Stories he was described as a magician, an alchemist and a Saint. These are important from the archetypal perspective because of the patterns that can be treced in the plot of the stories. The initiation process of İbni Sina to become an individulized person, according to the Campbell's formula is worthy in terms of the anima-anismus- shadow inner/total egotism and holy mother archetypes. Therefore, to analyze this text by decoding the hidden symbols the value of the text will be seen much clearly.
i?bn si?nâ hi?kâyeleri?ni?n arketi?psel tahli?li?
Keywords: Anima-animus and shadow arche-type; Collective unconscious; Noble individual; Tales of i?bni sina